Highly cross‐linked polyethylene is the new 'gold standard' bearing material for total hip arthroplasty. Issue 2 (28th May 2021) - Medley, John B.
Abstract: Conventional polyethylene is not used much in total hip arthroplasty (THA); it has been supplanted by oxidation‐resistant cross‐linked polyethylene (≥50 kGy irradiation). However, studies persist that de‐emphasize or ignore cross‐linked polyethylene. A selective literature review is used briefly to present the early use of conventional polyethylene and its implication in wear particle‐induced osteolysis leading to premature revision surgeries. The current situation is established based on Australian registry data and other studies that advocate the use of cross‐linked polyethylene in preference to conventional polyethylene. Although some studies suggest caution in using cross‐linked polyethylene, overall it is strongly supported. In the author's opinion, cross‐linked polyethylene is the new reference standard bearing material in THA.